Changing User Behavior in Decisions to Share COVID-19 Misinformation: An Implicit Association Test Study - Zaid Amin; Nazlena Mohamad Ali; Rahma Santhi Zinaida; Sulaiman Helmi (Postgraduate, University of Mataram, 2024)
Making medical decisions while distracted when receiving COVID-19 misinformation can majorly impact a person's life and even lead to death. Blatantly sharing COVID-19 misinformation is a significant problem of human behavior that triggers a speed-up and acceleration in the propagation and diffusion of misinformation in social media. While the latest research has focused on understanding the psychological dimensions of this phenomenon, few studies have explored the role of selective exposure and technological prevention when a person considers sharing COVID-19 misinformation, primarily through an Implicit Association Test (IAT). Our study identified and intervened in the association of user exposure between misinformation and implicit truth evaluations by using the Implicit Association Test (IAT) with